Memory in Leopard Geckos (Eublepharis macularius) in a Morris Water Maze Task - Eva Landová; Aleksandra Chomik; Barbora Vobrubová; Tereza Hruška Hášová; Monika Voňavková; Daniel Frynta; Petra Frýdlová (Animals)
The spatial orientation of mammals and birds has been intensively studied for many years, but the cognitive mechanism of spatial orientation and memory used by squamates remains poorly understood. Our study evaluated the learning and memory abilities of leopard geckos (Eublepharis macularius) in an adapted Morris water maze. The animals learned during the training phase consisted of 20 trials. To assess long-term memory, we retested geckos twice after several months. The geckos remembered the learned information in a short re-test after two months, but after four months, they required retraining to find the platform. We hypothesise that the duration of memory corresponds with short-term changes in semi-desert environments within one season, while disruption of memory performance after a six-month gap may simulate the more extensive seasonal change in spatial relationships in their natural environment. Moreover, during the winter period, geckos exhibit low activity, which can be connected with decreased frequency of foraging trips. Therefore, the memory loss after four months may reflect the low level of memory jogging. The motivation during the experiment was the crucial parameter of learning and memory processes. In later phases, geckos were less motivated to perform the task. Finally, they relearned the spatial orientation task, but they moved more slowly as the experiment progressed.